Development of mechanism for activation of participants’ interaction in innovative process at the regional level - Nurgalieva, S.Zh.; Bekniyazova, D.S.; Bespalyy, S.V. (BUKETOV BUSINESS REVIEW, 2021)
Objective: The research of efficiency of innovative activity in regions of Kazakhstan shows that at present time innovative infrastructure has been formed, but elements of the innovation infrastructure do not have important impact on innovative development of economy. In this regard, objective of research is to develop the model of functioning of regional scientific and technological park, contributing to full realization of innovative potential of country’s regions. Methods: In the course of research, suggesting a systematic approach to solving problems, ensuring unity of qualitative and quantitative methods, scientific methodology was used. In particular, index methods, methods of integral estimates, correlation and regression analysis (Pearson correlation coefficient), multiple correlation analysis were applied. Results: The paper proves that work of regional scientific and technology park contributes to commercialization of scientific developments of domestic scientists, which are confirmed by evaluation of its impact on innovative development of republic’s regions by conducting correlation and regression analysis. Conclusion: The creation of regional scientific and technology park will provide technological component in order to ensure the competitiveness of the economy of the country’s regions, owing to which it is possible to use intellectual potential of regions with full efficiency